Pengaruh Viral Marketing Dan Online Costumer Review Terhadap Keputusan Pembelian E-Commerce Shopee Pada Generasi Z Kota Mataram - Auliya Rohmatunnisa; Indah Ariffianti; I Made Suardana (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2025)
The study aims to test the effects of virmarketing and online custommer review on the purchase decisions of e-commerce shopee in the mataram city generation of z's, making the study variable 2 (two) an independent viral marketing (x1), online custommer review (x2) and the dependent variable of purchase decisions (y). The sample was taken using a nonsampling method with a kind of intergalactic sampling. Data gained by disseminating and filling out the Google form links to the 96 questionnaires on the z generation of mataram. Data analysis using linear regression. The study is determined that viral marketing with at count 5.425 > 1.985 t table, values 0,000<0.05, And an online costume review known value t count 6.678 > 1.985 t table, values 0,000<0.05. Indicating that viral marketing, custommer review online affected partial and simultaneous impact on purchase decisions. And dominant inan online costume review, its value is 0.497 greater than a viral marketing variable with a value of 0.404. The study has also been able to demonstrate that independent variables (viral marketing, online custommer review) can explain dependencies (purchasing decisions) by 60.7% while the rest by 39.3% are affected by other variables of the linear regression model.